A guideline framework for recognition, measurement and reporting of Malaysian government's property, plant and equipment under accrual accounting - Ismail, Suhaiza; Abdullah, Tahirah; Zainuddin, Siti Afiqah (Institut Perakaunan Negara, 2012)
This paper provides a framework for recognizing, measuring and reporting of Malaysian government’s non-current assets that are classified as property, plant and equipment. The framework which is mainly developed based on the International Public Sector Accounting Standard (IPSAS) 17 on Property, Plant and Equipment offers guidelines to interested parties on the appropriate accounting treatment for assets that fulfill the criteria of property, plant and equipment.